Integrasi Nilai Religius dalam Pembelajaran MI/SD untuk Membangun Karakter Siswa - sunarti narti 22; Ratmiati ratmiati; Husaini Husaini (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
ABSTRACT. This study aims to determine the integration patterns that can be applied by a teacher in the learning process. In this study the authors used the literature research method, with data collection techniques conducting a review of books, literature, notes related to the integration of religious values in shaping student character. Integration of religious values is the inclusion of values into the learning process so that children have character and behave based on good religious values. Through integration, it provides complex goals for learning outcomes, namely cognitive, affective and psychomotor. There are two patterns of integration that can be carried out by teachers in the learning process, namely: (1) inculcating religious values into teaching material, the meaning is when the teacher provides an explanation or the process of transferring knowledge, the teacher does not only provide knowledge, but the teacher instills religious values. inside it. (2) The use of Islamic symbols for learning content means the inculcation of religious values through the content in learning, such as questions or material examples using the Islamic symbols in Islam.Keywords: Integration, religious values, student character